LEARNING MALAYSIAN CULTURE AND ENGLISH LANGUAGE AT USM - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 23 February 2017 – Students from the Kyoto University of Foreign Studies (KUFS), Japan could now improve their skills in the English language from learning about the Malaysian culture at Universiti Sains Malaysia (USM).